PENGARUH EDUKASI BAHAYA ROKOK MENGGUNAKAN POSTER TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP TENTANG PENCEGAHAN MEROKOK REMAJA PUTRA SMAN 1 KOTA JAMBI - Vingky Arizalna (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aimed to determine the effect of smoking hazard education using poster media on improving knowledge and attitudes regarding smoking prevention among male adolescents at SMAN 1 Jambi City. The study applied a quantitative approach with a quasi-experimental one-group pretest-posttest design. The sample consisted of male students selected using a total sampling technique based on the research criteria. The intervention was delivered through educational posters containing information about cigarette substances, health risks, and smoking prevention efforts. Data were collected using knowledge and attitude questionnaires administered before and after the intervention. The results showed an increase in both knowledge and attitude scores after the poster-based education was provided. Statistical analysis indicated that poster media had a significant effect on improving knowledge and shaping positive attitudes toward smoking prevention among male adolescents. Therefore, posters can serve as an effective health promotion medium in the school environment, especially for adolescent smoking prevention programs.